Irradiation technique of constructional materials on the helium ions linac - Anokhin, R.А.; Dubniuk, S.M.; Zajtsev, B.V.; Pavlii, К.V. (Вопросы атомной науки и техники, 2016)
The irradiation technique of constructional materials on a helium ions LINAC is developed. Irradiations of metal, ceramic, and also semiconductor materials are carried out. During irradiation were measured: current of a ions beam, temperature of an exemplar and a slope angle of an exemplar to a beam axis. Also during experiments were controlled: an irradiation dose, profiles of a helium ion distribution and damage on exemplar thickness. Preliminary results show the considerable change of thermo-diffusion characteristics depending on beam energy and an irradiation dose. The phenomenological description of thermo-diffusion of the irradiated exemplars was offered.